Cefazolin in the treatment of central nervous system infections: A narrative review and recommendation. Issue 1 (22nd January 2023) - Antosz, Kayla; Battle, Sarah; Chang, Jack; Scheetz, Marc H.; Al‐Hasan, Majdi; Bookstaver, P. Brandon
Abstract: Infections of the central nervous system (CNS) are complex to treat and associated with significant morbidity and mortality. Historically, antistaphylococcal penicillins such as nafcillin were recommended for the treatment of methicillin‐susceptible staphylococcal CNS infections. However, the use of antistaphylococcal penicillins presents challenges, such as frequent dosing administration and adverse events with protracted use. This narrative reviews available clinical and pharmacokinetic/pharmacodynamic (PK/PD) data for cefazolin in CNS infections and produces a recommendation for use. Based on the limited available evidence analyzed, dose optimized cefazolin is likely a safe and effective alternative to antistaphylococcal penicillins for a variety of CNS infections due to methicillin‐susceptible Staphylococcus aureus . Given the site of infection and wide therapeutic index of cefazolin, practitioners may consider dosing cefazolin regimens of 2 g IV every 6 h or a continuous infusion of 8–10 g daily instead of 2 g IV every 8 h to optimize PK/PD properties.